DIAGNOSING OF BASIC AND SPECIFIC MOTORIC CAPABILITIES AT THE YOUTH OF THE BASKETBALL SCHOOL - Florian Miftari; Hasim Rushiti; Bahri Gjinovci (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
In general the problematic of diagnosing basic and specific motor movement information of the basketball game in found in the works of a considerable number of world authors. In this work a youth population of an age group between 13-14 years old will be treated. The total number of participants is defined to an amount of 100 of young basketball players, members of two different basketball academies. In this experiment, the subjects will conduct tests in 5 basic motor skills variables such as: 1. Steady Jump in length, 2 steady jump in height 3.20 meters run from a steady start, 4. Medicine Ball Throw and 5. Agility Test. While from specific motor movement skills are included: 1.20 Meters run with ball, 2. Basketball shooting for 30 seconds round-trip,3. Anaerobic durability with and without ball (kamikaze) 4. Intensive Basketball shots-Change of direction and 5. Basketball shots from five positions. Subject to the number of subjects that will be treated in this study, their age and the amount of variables tested, the main objectives of this study, will be limited to achieving the goals. On the basis of test results, it can be concluded that there are no significant differences in the basic motor parameters between the two groups G1 and G2, mostly due to systematic practice effects rather than academy belonging itself.In the other hand, differences between the two groups in the specific basketball motor skills can be clearly identified, in typical basketball movement situations.In addition, comparing the test results of the individuals tested for the purpose if this diagnosis, a much more advanced level of motor skills compared to the normal population of the same group age that don't engage in basketball activities can be identified. This experimental study carried out in the youth in the age group of 13(-+ 6 months) years old that continuously in a systematic manner attend basketball academies in two different basketball schools, with sustainable arguments can show the importance of systematic valuation in order to solve many arising problems such as: planning, programming, developing and controlling the effects of training work. Specifically, it is of utmost importance to continously monitor the development of motor skills in the youth.